Assessing 2016 drought progression over India using remote sensing data for the period 2006-2015 - De Azevedo, Samara C. [UNESP]; Singh, Ramesh P.; Da Silva, Erivaldo A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Drought occurrence is a gradual process with long-lasting effects and satellite remote sensing data help in the monitoring and severity of drought conditions. This paper analyzes MODIS (Moderate Resolution Imaging Spectroradiometer) satellite data to study the vegetation stress associated with drought conditions over India. Dynamics of monthly Normalized Difference Vegetation Index (NDVI) and its association with climate conditions over 10 years period have been studied. We have considered satellite data for the period 2006-2015 from three highly stressed NDVI regions based on seasonal NDVI difference from 2015-2016. The drought conditions correspond to the pronounced changes in weather parameters (land surface temperature, air temperature, and relative humidity) and adjacent sea surface temperature. The detailed analysis of these parameters shows a close relation with reduction upto 13% in NDVI values in 2016 associated with a pronounced reduction in precipitation and increase in surface temperature.
Keywords: Drought; India; LST; MODIS NDVI